On the Interaction Between Dissipation and Supply Agents in Some Nonlinear Evolution Problems (Journal of Partial Differential Equations, 1993)
The paper deals with typical examples of semilinear evolution systems possessing solutions which behave at the interior of the considered domain unlike they do at its boundary. Sharp conditions arc obtained which guarantee interior boundedness of a solution component despite the growth of corresponding data as well as ensure strict interior positivity of a solution component despite its decay at the boundary.